History of Czech anatomical terminology - Musil, Vladimír (Anatomical science international, 2024)
Latin anatomical terminology has been codified since 1895. However, the situation is different for national anatomical terminologies. There are countries that have standardized anatomical terminology in their language, e.g., Poland, Slovenia, Japan, Spain, Hungary, others, such as the Czech Republic or Slovakia, are still lacking their own standardized and official terminology. In the Bohemian Lands, the first terms describing parts of the human body appeared as early as the ninth century in works written in Cyrillic script. The first comprehensive references to Czech anatomical terminology appeared in the fourteenth century. From the Baroque period, anatomical terms were preserved in the educational works of the Teacher of Nations Jan Amos Comenius' Janua linguarum reserata and Orbis sensualium pictus. Many of these terms have remained almost unchanged to this day, but some of them have acquired a pejorative meaning over time. We present here an overview of the history and examples of these terms describing parts of the human body.
Keywords: dějiny středověku; History, 16th Century; anatomie; dějiny 16. století; History, Medieval; History, 20th Century; dějiny 20. století; Terminology as Topic; Česká republika; Bohemian Lands; terminologie jako téma; History, 15th Century; dějiny 17. století; Czech anatomical terminology; Czech Republic; Anatomy; dějiny 19. století; dějiny 18. století; Humans; History, 18th Century; History, 17th Century; dějiny 15. století; History; lidé; History, 19th Century